Analysis Of The Judge's Considerations In Imposing Criminal Sentences On Perpetrators Of The Criminal Acts Of Human Trafficking Related To Online Prostitution Through The Michat Application (Decision Study Number: 892/Pid.Sus/2024/PN.Tjk - Baharudin; Andi Kurniawan (International Journal of Education, Vocational and Social Science, 2026)
The phenomenon of human trafficking (TPPO) is considered an extraordinary crime due to its complex and multidimensional characteristics. TPPO does not only involve individual perpetrators, but is often carried out through organized criminal networks that have certain structures, roles, and strategies in recruiting, moving, and exploiting victims. The formulation of the problem in this study is what is the basis for the Judge's considerations in sentencing perpetrators of human trafficking related to online prostitution through the Michat application based on Decision Number: 892 / Pid.Sus / 2024 / PN.Tjk? and how is the relevance of the Judge's considerations in sentencing perpetrators of human trafficking related to online prostitution through the Michat application reviewed from the aspects of legal certainty, justice, and benefit in Decision Number: 892 / Pid.Sus / 2024 / PN.Tjk?. The research method uses a normative and empirical juridical approach. The types of data used are secondary data and primary data. Data collection through library research and field research. The data analysis used is qualitative juridical. Based on the results of the research and discussion, conclusions can be drawn, including the basis for the Judge's considerations in sentencing the perpetrator of the crime of human trafficking related to online prostitution through the Michat application based on Decision Number: 892/Pid.Sus/2024/PN.Tjk covering legal aspects, facts, and the purpose of the sentence. From a legal perspective, the judge referred to Law Number 21 of 2007 concerning the Eradication of Human Trafficking, Law Number 44 of 2008 concerning Pornography, and the ITE Law so that the defendant's actions are clearly qualified as human trafficking and digital-based pornography violations. From a factual perspective, the judge assessed the trial evidence that showed the recruitment, transportation, and exploitation of victims through the Michat application, as well as the victim's socially and psychologically vulnerable condition. Considerations for the purpose of sentencing include general prevention, specific prevention, and protection and rehabilitation of victims. The relevance of the Judge's considerations in sentencing perpetrators of human trafficking related to online prostitution through the Michat application is reviewed from the aspects of legal certainty, justice, and benefit in Decision Number: 892/Pid.Sus/2024/PN.Tjk. Legal certainty is reflected in the consistent application of the Human Trafficking Law, the Pornography Law, and the ITE Law. Justice is demonstrated through protection of victims and the imposition of proportional sentences for perpetrators. The benefits of law are seen from the preventive, corrective, and rehabilitative objectives of criminal law, as well as providing a deterrent effect for perpetrators and the community. Based on the above conclusions, it can be suggested that law enforcement officers are expected to increase the systematic collection of digital evidence and strengthen psychological assistance and protection for victims to support an effective judicial process. Judges are advised to integrate legal certainty, justice, and benefit in criminal decisions through the application of consistent procedural standards, victim protection, and prevention and rehabilitation programs oriented towards social benefits and a deterrent effect.